CHF enhancement by honeycomb porous plate in saturated pool boiling of nanofluid - Mori, Shoji; Mt Aznam, Suazlan; Yanagisawa, Ryuta; Okuyama, Kunito (Taylor and Francis Ltd., 2016)
One strategy for severe accidents is in-vessel retention (IVR) of corium debris. In order to enhance the capability of IVR in the case of a severe accident involving a light-water reactor, methods to increase the critical heat flux (CHF) should be considered. Approaches for increasing the IVR capability must be simple and installable at low cost. Moreover, cooling techniques for IVR should be applicable to a large heated surface. Therefore, as a suitable cooling technology for required conditions, we proposed cooling approaches using a honeycomb porous plate for the CHF enhancement of a large heated surface in a saturated pool boil- ing of pure water. In this paper, CHF enhancement by the attachment of a honeycomb-structured porous plate to a heated surface in saturated pool boiling of a TiO-water nanofluid was investigated experimentally under atmospheric pressure. As a result, the CHF with a honeycomb porous plate increases as the nanoparticle concentration increases. The CHF is enhanced significantly up to 3.2 MW/m2 at maximum upon the attachment of a honeycomb porous plate with 0.1 vol.% nanofluid. To the best of the author’s knowledge, under atmospheric pressure, a CHF of 3.2 MW/m2 is the highest value for a relatively large heated surface having a diameter exceeding 30 mm.